2011
DOI: 10.1111/j.1475-5661.2011.00490.x
|View full text |Cite
|
Sign up to set email alerts
|

The reputational ghetto: territorial stigmatisation in St Paul’s, Bristol

Abstract: This paper intervenes in the debate on ethnic segregation in British cities by paying attention to the hitherto neglected phenomenon of territorial stigmatisation. It discusses the stigma attached to the neighbourhood of St Paul's, Bristol; how it emerged, how it is felt and negotiated by local residents 'from below', and its effects on how that neighbourhood is managed by policy elites 'from above'. The paper critically reviews some recent influential treatments of ethnic segregation in the UK and the moral p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
104
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(106 citation statements)
references
References 43 publications
1
104
0
1
Order By: Relevance
“…Since then, the word "ghetto" has always had a component of segregation in its meaning, and an unmistakably negative connotation. However, their findings indicated that segregation was low in these selected neighborhoods, and it's fair to say that segregation is low within the Rockwood neighborhood as well (it might be where many Portland metro area Latinos live, but demographically overall, it is quite diverse relative to many other Portland area neighborhoods), but ultimately, media narratives that emerged in all cases created a lasting impression among area residents (Slater and Anderson 2011).…”
Section: Rockwood's Futurementioning
confidence: 99%
“…Since then, the word "ghetto" has always had a component of segregation in its meaning, and an unmistakably negative connotation. However, their findings indicated that segregation was low in these selected neighborhoods, and it's fair to say that segregation is low within the Rockwood neighborhood as well (it might be where many Portland metro area Latinos live, but demographically overall, it is quite diverse relative to many other Portland area neighborhoods), but ultimately, media narratives that emerged in all cases created a lasting impression among area residents (Slater and Anderson 2011).…”
Section: Rockwood's Futurementioning
confidence: 99%
“…Growing importance of cities, rural-urban migration and the changes that it brings about in public consciousness are often studied by economists, geographers, psychologists, sociologists, and linguists. Some of these studies are concerned with the problems of the city's image and its elements (Kevin Lynch, 1960;Avraham 2004;Evans and Show, 2004;Garcia, 2004Garcia, , 2005Dinnie, 2010;Duncan and Ley, 2013), the influence of the city's history, values and attitudes on the city's image, emotional attitude towards urban areas (Strauss, 1968;Van der Ryn, 1963;Pile, 2010;Slater and Anderson, 2012), the impact of age, gender, occupation on the perception of the city (Appleyard, 1970). Very often, the studies of urbanization are not limited to the analysis of urban areas and characteristics of urban living.…”
Section: Introductionmentioning
confidence: 99%
“…The statistical construction and deconstruction of the British "ghetto" has been the subject of intensifying academic and policy examination over the past two decades, which has yielded a substantial body of quantitative (Finney andSimpson 2009a, 2009b;Johnson et al 2005;Mateos et al 2009;Peach 2009;Simpson 2007) and qualitative (Phillips 2007;Phillips et al 2007;Slater and Anderson 2012) research, however, approaches to the study of segregation that seek to marry these perspectives remain elusive. For many cultural geographers, statistical analysis of migrant residence are too blunt an instrument to understand the vagaries of the housing market (Bolt et al 2010: 170;Phillips et al 2007: 218) and thus scholarship has largely followed parallel modus operandi.…”
Section: Contextsmentioning
confidence: 99%
“…At the qualitative level, the work of the urban sociologist Loïc Wacquant (2008) has been a powerful influence for a new wave of scholarship in Britain focusing on the racialization of inner city areas and the impact of "territorial stigmatization" by the state and media (Slater and Anderson 2012). Wacquant has drawn parallels between Manchester's Moss Side and various other urban "neighbourhoods of relegation" in which the "spatial stigma" experienced by the residents of such areas transcends ethnic boundaries to encompass broader socioeconomic spatial divisions (2007: 116; 2008: 241).…”
Section: Contextsmentioning
confidence: 99%